ANALISIS KEBERHASILAN IMPLEMENTASI MODEL PROJECT BASED LEARNING (PJBL) DALAM PENDIDIKAN JASMANI, KESEHATAN, DAN REKREASI (PJKR) DI PERGURUAN TINGGI - Tri Alim Saputra Hidayat; Rahmat Syaifudin; Didik Cahyono; M. Torero Rigel Centeury; Muhammad Rifai; Ahmad Junaidi (EDU RESEARCH, 2024)
This study aims to analyse the successful implementation of Project Based Learning (PjBL) model in Physical Education, Health and Recreation (PJKR) study programmes in higher education. The PjBL model is considered suitable for achieving comprehensive learning objectives in the field of PJKR, but its success needs to be studied more deeply. This literature review includes a review of the concepts and characteristics of the PjBL model, as well as its potential in the context of CHDR in higher education. Various supporting factors and challenges that influence the implementation of PjBL in CHDR learning are identified through literature analysis. The results of the study indicate that the implementation of the PjBL model in CHDR can increase students' active involvement, develop holistic competencies, and encourage meaningful and contextualised learning. However, careful planning, infrastructure support, and the role of competent lecturers are needed to achieve successful implementation. In addition, challenges such as time allocation, project management, and appropriate assessment must be overcome for the PjBL model to be implemented effectively. This study concludes that the implementation of the PjBL model in CHDR in higher education has great potential, but requires comprehensive preparation and strategies to ensure its success. Recommendations for future research include empirical studies on the impact of PjBL implementation on the learning outcomes of PJKR students.